MATHEMATICAL LITERACY: THE EXPERIENCE OF INTERPRETATION - Dieorditsa, Taiana; Tolmachov, Volodimir (Physical and Mathematical Education, 2024)
Formulation of the problem. In 2016, Ukraine joined the Programme for International Student Assessment (PISA). The evaluation system of the program is based on a logical foundation, the frame of which is the concept of «literacy». Thus, the objects of assessment of students' achievements in reading, mathematics, and science in PISA documents are designated by the terms «reading literacy», «mathematical literacy» and «scientific literacy», respectively. Given that there is no universal definition for the term «mathematical literacy», we wondered: what are the essential features of mathematical literacy covered by the semantic content of this term?Materials and methods. For the analytical study of the concept of mathematical literacy set out in the framework documents in mathematics PISA/UCEQA (2018, 2022), we used the method of interpretation, focusing on the making of the semantic content of the term under study. In the theory of the notion, the semantic content is considered as the third main characteristic of the term, which contains the essential signs of the notion it labelled. For the term «mathematical literacy» we derived them, using four logical operations based on both types of hierarchical relations between the notions — «genus — species» and «whole-part». Here is a list of them: generalization of the notion, taxonomic and mereological divisions, and mereological integration. The idea of their application arises from the general morphological analysis of F. Zwicky.To graphically depict the structure of the semantic content of the term under study, we used a mind map.Results. The result of the interpretation of the term «mathematical literacy» is presented as a verbal and graphic representation of its semantic content. The result of the generalization of the notion denoted by this term: the closest genus is «intellectual ability». Examples of other species of this kind are rational thinking and wit. The result of the taxonomic division: based on the «ability to mathematize the situation» within the scope of the notion of «mathematical literacy», two forms of thinking are distinguished — mathematical and computational. The result of the mereological division: mathematical literacy as the ability to solve real everyday problems with a mathematical component is possible by seven general mathematical skills. The result of mereological integration: mathematical literacy is a component of the system of educational achievements of the individual in mathematics. Other components of this system are mathematical competence and mathematical culture. We believe that the purpose of teaching mathematical literacy is to educate students on intellectual habits and consolidate them on mathematical content.Conclusion. When we use the term «mathematical literacy», we are referring to a young person who is proficient in mathematical and computational ways of thinking to some extent; She has mastered basic mathematical skills at an acceptable level and therefore is able to solve ordinary problems with a mathematical component, which occur in different contexts of her reality. Being skilled in mathematics, this person does not agree to a routine joyless life but strives to successfully realize himself in its various areas.
Keywords: literacy; intellect; thinking; habits of mind; mathematization; problem solving